(untitled) (Historia, 2021)
The outposts in the service of the Cape Refreshment Station, 1652-1795. The outposts (buitenposten) f the VOC at the Cape, of which 57 were identified by the author, can be defined as manned, decentralised and specialised auxiliary service stations. Their functions included military guard and signal duties, the production of vegetables, timber, fuel and building materials, organising and providing transport for the headquarters, conducting trading expeditions to the Khoi and rescue operations for shipwrecked crews and cargo, collecting specimens for professors of natural history at European universities, herding the Company’s cattle and sheep, and fishing. These outposts, particularly the military posts representing the vac at great distances from the Castle in the Table Valley, marked the advancing frontier and played no small part in the decline of the social and economic structures of the aboriginal Khoi. The Cape service station would not have succeeded as it did without the use of the outpost-system, as there was no other way of protecting resources against rivals than by occupying them, there was no alternative labour force, no economic structure that provided maritime services, no other system capable of handling heavy transport, no ally on the borders to share the military pressures, and (early on) no other agricultural producer, that would have enabled the Company to buy rather than to cultivate. Unfortunately the production side of the outpost-system outlived its need and led to the serious retarding of local commercial, industrial and agricultural development and marketing systems.